2007
DOI: 10.1017/s1751731107284058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complete feed blocks or grazing and supplementation of lambs on performance, nutrient utilisation, rumen fermentation and rumen microbial enzymes

Abstract: A study to compare two feeding systems, stall feeding (SF) and grazing plus supplementation (GR) was carried out, based on intake, performance and rumen fermentation characteristics of lambs. While SF animals received ad libitum complete feed blocks (CFB), GR animals were allowed grazing for 8 h on a pasture and supplemented with concentrate mixture at 250 g per head per day. Intake in grazing animals was determined using chromium III oxide as internal marker. Intake of dry matter (DM), crude protein (CP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Furthermore, it has been reported that supplementation of the complete feed in block form during feed scarcity in semi-arid region helped grazing ewes to maintain their body weight (BW) compared to unsupplemented ewes [38]. Feeding complete feeds appear superior to grazing plus supplementation in terms of dry matter (DM)/nutrient intakes and animal performance, thus can be recommended as an alternative to such feeding strategy for sheep production, especially where the pastures are highly eroded and need resting for regeneration or curing [37,39]. …”
Section: Benefits Of Complete Feed Systemmentioning
confidence: 99%
“…Furthermore, it has been reported that supplementation of the complete feed in block form during feed scarcity in semi-arid region helped grazing ewes to maintain their body weight (BW) compared to unsupplemented ewes [38]. Feeding complete feeds appear superior to grazing plus supplementation in terms of dry matter (DM)/nutrient intakes and animal performance, thus can be recommended as an alternative to such feeding strategy for sheep production, especially where the pastures are highly eroded and need resting for regeneration or curing [37,39]. …”
Section: Benefits Of Complete Feed Systemmentioning
confidence: 99%
“…Although some studies have described the rumen microbial ecosystem under grazing and feeding regimes in cattle [24], sheep [61], cows [4,16] and yak [17] by Sanger sequencing and qPCR methods, HTS technology has not yet been used to provide comparisons concerning microbial community compositions and diversity in yaks and Tibetan sheep under different feeding paradigms. Therefore, this study investigated the 16S rRNA gene in the rumen prokaryotic communities of these two ruminants using the high-throughput sequencing technique under conditions of natural grazing and barn feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Fanchone@antilles.inra.fr In the same way, in direct comparisons between animals fed indoors and animals fed at pasture, the animals fed indoors often received a high proportion of supplements, whereas animals at pasture did not (Keane and Allen, 1998;Zervas et al, 1999;Moniruzzaman et al, 2002;Raghuvansi et al, 2007). In addition, the forage on offer was not the same indoors and at pasture.…”
Section: Introductionmentioning
confidence: 99%